Faculty as global learners : off-campus study leaders at liberal arts colleges - Gillespie, Joan (Higher education consultant); Jasinski, Lisa; Gross, Dana Lynn (Lever Press, 2020)
This co-authored collection offers valuable insights about the impact of leading off-campus study on faculty leaders' teaching, research, service, and overall well-being. Recognizing that faculty leaders are themselves global learners, the book addresses ways that liberal arts colleges can more effectively achieve their strategic goals for students' global learning by intentionally anticipating and supporting the needs of faculty leaders, as they grow and change. Faculty as Global Learners offers key findings and recommendations to stimulate conversations among administrators, faculty, and staff about concrete actions they can explore and steps they can take on their campuses to both support faculty leaders of off-campus programs and advance strategic institutional goals for global learning. This collection includes transferrable pedagogical insights and the perspectives of faculty members who have led off-campus study programs in a variety of disciplines and geographic regions.